Comprehensive analysis of the Kinetoplastea intron landscape reveals a novel intron-containing gene and the first exclusively trans-splicing eukaryote - Kostygov, Alexei Yu; Skýpalová, Karolína; Kraeva, Natalia; Kalita, Elora; McLeod, Cameron; Yurchenko, Vyacheslav; Field, Mark C; Lukeš, Julius; Butenko, Anzhelika (BMC biology, 2024)
BACKGROUND: In trypanosomatids, a group of unicellular eukaryotes that includes numerous important human parasites, cis-splicing has been previously reported for only two genes: a poly(A) polymerase and an RNA helicase. Conversely, trans-splicing, which involves the attachment of a spliced leader sequence, is observed for nearly every protein-coding transcript. So far, our understanding of splicing in this protistan group has stemmed from the analysis of only a few medically relevant species. In this study, we used an extensive dataset encompassing all described trypanosomatid genera to investigate the distribution of intron-containing genes and the evolution of splice sites. RESULTS: We identified a new conserved intron-containing gene encoding an RNA-binding protein that is universally present in Kinetoplastea. We show that Perkinsela sp., a kinetoplastid endosymbiont of Amoebozoa, represents the first eukaryote completely devoid of cis-splicing, yet still preserving trans-splicing. We also provided evidence for reverse transcriptase-mediated intron loss in Kinetoplastea, extensive conservation of 5' splice sites, and the presence of non-coding RNAs within a subset of retained trypanosomatid introns. CONCLUSIONS: All three intron-containing genes identified in Kinetoplastea encode RNA-interacting proteins, with a potential to fine-tune the expression of multiple genes, thus challenging the perception of cis-splicing in these protists as a mere evolutionary relic. We suggest that there is a selective pressure to retain cis-splicing in trypanosomatids and that this is likely associated with overall control of mRNA processing. Our study provides new insights into the evolution of introns and, consequently, the regulation of gene expression in eukaryotes.
Keywords: Genes, Protozoan; fylogeneze; Phylogeny; Trans-Splicing; Kinetoplastida; Trypanosomatidae; molekulární evoluce; Evolution, Molecular; protozoální proteiny; Introns; Splicing; RNA helicase; protozoální geny; introny; Trypanosomatina; RNA-binding protein; Kinetoplastea; Protozoan Proteins; Poly(A) polymerase; trans-splicing